Following Rapoport's Rule: the geographic range and genome size of bacterial taxa decline at warmer latitudes. (27th June 2017) - Lear, Gavin; Lau, Kelvin; Perchec, Anne‐Marie; Buckley, Hannah L.; Case, Bradley S.; Neale, Martin; Fierer, Noah; Leff, Jonathan W.; Handley, Kim M.; Lewis, Gillian
Summary: We sought to test whether stream bacterial communities conform to Rapoport's Rule, a pattern commonly observed for plants and animals whereby taxa exhibit decreased latitudinal range sizes closer to the equator. Using a DNA sequencing approach, we explored the biogeography of biofilm bacterial communities in 204 streams across a ∼1000 km latitudinal gradient. The range sizes of bacterial taxa were strongly correlated with latitude, decreasing closer to the equator, which coincided with a greater than fivefold increase in bacterial taxonomic richness. The relative richness and range size of bacteria were associated with spatially correlated variation in temperature and rainfall. These patterns were observed despite enormous variability in catchment environmental characteristics. Similar results were obtained when restricting the same analyses to native forest catchments, thereby controlling for spatial biases in land use. We analysed genomic data from ∼500 taxa detected in this study, for which data were available and found that bacterial communities at cooler latitudes also tended to possess greater potential metabolic potential. Collectively, these data provide the first evidence of latitudinal variation in the range size distributions of freshwater bacteria, a trend which may be determined, in part, by a trade‐off between bacterial genome size and local variation in climatic conditions.